Emerging European financial markets independence and integration post-enlargement - Batten, Jonathan A.; Kearney, Colm (Emerald, 2006)
This volume is concerned with contributing to the growing body of literature that examines the extent of, and the implications of enhanced independence and integration that will result from the recent EU enlargement for the development of emerging European financial markets. The objective is to provide a perspective on the nature and complex problems associated with financial market development in the emerging European economies and their relationships with the EU (and other major regions) in the post-EU enlargement environment. The volume is divided into five parts. Part A focuses on the important implications for fiscal policy, part B deals with monetary policy and banking, part C explores issues concerned with financial innovation and liberalization, part D examines recent developments in equity market integration, and part E looks at the implications. It fills a substantial gap in this field. Broad in scope, it serves as an invaluable reference for those interested in European Financial Markets.
Keywords: Business & Economics -- Finance.; Finance.; Financial institutions -- Europe.; elektronické knihy; electronic books